Strategi Pembelajaran Anak Usia Dini Sebagai Panduan Bagi Orang Tua - Siahaan, Hasnah; Nayla Zaskia Siregar , Fatimah; Pratiwi , Sindi; Nadillah Selian , Suci; Afifah , Zahra (Jurnal Al-Kifayah: Ilmu Tarbiyah dan Keguruan, 2023)
Parenting patterns that make children achieve learning. Therefore this strategy becomes a guide for parents to educate their children. The method used is qualitative. With the method used by the author, at least making several references, with data referred to from books or journals. The strategy used to make parents aware of the behavior of their children. Some of the theories that have been described can be used as information. A guide for parents of children that makes their development maximized in a good way